Comprehensive evaluation of Bletilla striata and its substitutes by combining phenotypic characteristic, chemical composition, and anti-melanogenic activity. (March 2022) - Wang, Rongbin; Qin, Yadong; Zhou, Juanjuan; Wang, Juan; Shu, Huiyun; Zhou, Shoubiao; Peng, Xin
Abstract: Bletilla striata is a precious traditional Chinese medical herb with a wide range of applications in pharmacological and cosmetic fields. Because of the shortage of resources, Bletilla ochracea and Bletilla formosanare are also used as the substitutes. To distinguish the differences and homologies, the typical morphologic and microscopic characteristics of them were compared, and a UPLC fingerprint analysis coupled with chemometric methods were developed for characterization and quality evaluation of Bletillae Rhizoma. Gastrodin, protocatechuic acid, gymnoside V, blestrianol A, coelonin, gymnosides Ⅸ and batatasin II were identified as the potential chemical markers for comprehensive quality evaluation by ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS). The anti-melanogenic activities of the three species were also compared for the first time in vivo using the zebrafish model, the results suggested that B. striata and its two substitutes had obvious anti-melanogenic activities, and they were not-toxic at depigmenting doses. Molecular docking studies revealed batatasin III, blestrianol A, coelonin, and gastrodin were possible multitarget compounds associated with melanogenesis suppression, which are important for their potential future medical application. Graphical abstract: Image 1 Highlights: B.ochracea has a relatively lower component similarity with B.striata than that of B. formosana . B.striata and its two substitutes had obvious anti-melanogenic activities. Batatasin III,  blestrianol A, coelonin, and gastrodin were possible anti-melanogenic activity ingredients.